2022
DOI: 10.3390/nano12183244
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Zn-Doped ITO Sol–Gel Films Deposited on Different Substrates: Application as CO2-Sensing Material

Abstract: Undoped and Zn-doped ITO (ITO:Zn) multifunctional thin films were successfully synthesized using the sol–gel and dipping method on three different types of substrates (glass, SiO2/glass, and Si). The effect of Zn doping on the optoelectronic, microstructural, and gas-sensing properties of the films was investigated using X-ray diffraction (XRD), atomic force microscopy (AFM), scanning electron microscopy (SEM), transmission electron microscopy (TEM), spectroscopic ellipsometry (SE), Raman spectroscopy, Hall ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…39 Thus, we believe that the liquid contact in the printing process mitigates the effects of the long alkyl chains and creates a good interface regardless of the existing long alkyl chains. Besides, according to the previous research relationship to the Zn-doped ITO by solution processing, 40,41 the electrical parameters, such as carrier concentration and conductivity, can be enhanced by Zn doping due to lowered film porosity. We consider this doping effect is also able to obtain good electrical characteristics.…”
Section: Resultsmentioning
confidence: 94%
“…39 Thus, we believe that the liquid contact in the printing process mitigates the effects of the long alkyl chains and creates a good interface regardless of the existing long alkyl chains. Besides, according to the previous research relationship to the Zn-doped ITO by solution processing, 40,41 the electrical parameters, such as carrier concentration and conductivity, can be enhanced by Zn doping due to lowered film porosity. We consider this doping effect is also able to obtain good electrical characteristics.…”
Section: Resultsmentioning
confidence: 94%
“…Different substrates (Si, SiO 2 /glass, and glass) were coated by five successive layers using the ITO/Nb sol–gel solution. To highlight the influence of the dopant on the ITO film structure, previously reported data [ 30 ] on the undoped ITO thin films are presented in Figure 1 . The diffraction lines, corresponding to crystal planes (2 2 2), (4 0 0), (4 4 0), and (6 2 2), were observed for both ITO/Nb and ITO thin films.…”
Section: Resultsmentioning
confidence: 99%
“…The morphology of the layer-by-layer deposited ITO film is strongly affected by the crystal growth process, because the final size of the ITO crystallites is bigger than the initial thickness of each deposited layer (about 5 nm). If we compare these results with the case of Zn-doped ITO films [ 30 ], it can be observed that the crystallization process and the total film thickness are influenced by the dopant nature [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations